Blasphemy and Persecution: Insights from 'The Message' on Freedom of Religion, Women’s Rights, and Martyrdom in Early Islam - Misbahu Ismail (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2025)
At a time when Muhammad was approaching the Quraysh worshipping in the Ka’abah, the voice of a woman from the inside reacted: “to challenge the gods within the earshot of gods is dangerous. Unreasonable, Rebellious, Blasphemous”! The Prophet of Islam, Muhammad (peace be upon him and his noble family and companions), was the first in the history of Islam to be accused of committing blasphemy against ‘gods’ and ‘goddesses’. His scanty following too, were accused of committing blasphemy and were brutally persecuted by the ruling Arab tribal confederation (the Quraysh) of Makkah at the time. The pattern of persecution to some extent equates the recent term of ‘jungle justice’ especially attributed to alleged blasphemers in Nigeria. The study of a documentary on the history of Muhammad and his struggle to establish Islam, titled ‘The Message’ (Arabic: ‘Risalah’), provides greater insights on the meaning of blasphemy and its implications on freedom of religion or belief (FORB), the right of women and slaves as well as the concept of martyrdom as a consolation to paradise. This paper sheds an interesting light on blasphemy in the context of this documentary, as well as illustrates its significance to the understanding of the Islamic position on Forb, the concept of martyrdom and the right of women and slaves.